Pengaruh Kompetensi, Disiplin Kerja dan Budaya Kerja Terhadap Kinerja Pegawai pada IAIN Sorong - Sahid, Radiah (JURNAL ILMIAH GEMA PERENCANA, 2022)
This study aims to analyze: 1) The influence of Competence, Work Discipline, and Work Culture partially on Employee Performance at the Sorong State Islamic Institute, 2) The influence of Competence, Work Discipline, and Work Culture simultaneously on Employee Performance at the Sorong State Islamic Institute, 3) The most dominant variable has an effect on employee performance at the Sorong State Islamic Institute. The results of the study show that: 1) Competence partially has a positive and significant effect on the Performance variable; 2) Partially, Work Discipline Variables have a positive and significant effect on the Performance variable, 3) Partially, Work Culture has a positive and significant effect on the Performance variable, 4) Simultaneously Competence, Work Discipline, and Work Culture have a positive and significant effect on performance, 5) Variables The most dominant that affects performance is Work Discipline, 6) The coefficient of determination shows that 53.7% of employee performance variables can be explained by independent variables, namely Competence (X1), Work Discipline (X2), Work Culture (X3) while the remaining 46.3% is explained by other variables outside the model. This study uses an associative approach with a quantitative model. Associative research according to Sugiyono (2013) is "research that aims to determine the relationship between two or more variables". According to Echdar (2017), the quantitative approach is "a method that places more emphasis on aspects of objective measurement of social phenomena, in which every social phenomenon is described in several problem components, variables, and indicators".